2010
DOI: 10.1007/s00442-010-1758-2
|View full text |Cite
|
Sign up to set email alerts
|

Sand and sandbar willow: a feedback loop amplifies environmental sensitivity at the riparian interface

Abstract: Riparian or streamside zones support dynamic ecosystems with three interacting components: flowing water, alluvia (river-transported sediments), and vegetation. River damming influences all three, and subsequent responses can provide insight into underlying processes. We investigated these components along the 315-km Hells Canyon corridor of the Snake River that included reaches upstream, along, and downstream from three large dams and reservoirs, and along the Salmon River, a free-flowing tributary. Sandbar w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 42 publications
2
41
1
Order By: Relevance
“…However, specific responses depend upon depth-togroundwater and individual differences amongst functional types; for example, riparian cottonwood trees (P. fremontii) responded to rewetting with growth that was larger and faster than the response of co-occurring willow (S. exigua), a smallstature, thicket-forming shrub that is restricted to streamside areas with very shallow groundwater (Scurlock, 1998;Rood et al, 2011). From an understanding of the relationships between tree growth and depth-to-groundwater, historical periods of sensitivity to hydrological drought (i.e.…”
Section: Effects Of Groundwater On Growth and Dendrochronological Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, specific responses depend upon depth-togroundwater and individual differences amongst functional types; for example, riparian cottonwood trees (P. fremontii) responded to rewetting with growth that was larger and faster than the response of co-occurring willow (S. exigua), a smallstature, thicket-forming shrub that is restricted to streamside areas with very shallow groundwater (Scurlock, 1998;Rood et al, 2011). From an understanding of the relationships between tree growth and depth-to-groundwater, historical periods of sensitivity to hydrological drought (i.e.…”
Section: Effects Of Groundwater On Growth and Dendrochronological Traitsmentioning
confidence: 99%
“…can be very sensitive to groundwater decline, resulting in reductions of ET, productivity and canopy conductance as a consequence of increases in vapour pressure deficit that are correlated with depth-to-groundwater (Gazal et al, 2006;Kochendorfer et al, 2011). Branch sacrifice, partial crown dieback and mortality commonly occur in Populus following substantial groundwater drawdown (Mahoney and Rood, 1991;Kranjcec et al, 1998;Scott et al, 1999;Rood et al, 2000Rood et al, , 2003Cooper et al, 2003). However, stomatal closure and crown dieback in Populus can prevent total hydraulic failure, and thereby minimise mortality rates, by maintaining favourable xylem water potentials within the remainder of the crown (Amlin and Rood, 2003).…”
Section: The Gnangara Moundmentioning
confidence: 99%
“…"NPMR generally performs well at both spatial scales and that distributions of non-indigenous species are predicted as well as those of native species." Rood et al (2010) http://dx.doi.org/10.1007/s00442-010-1758-2 quantitative (willow cover) Local mean NPMR with Gaussian weights, regressing willow cover against environmental variables. Illustrations include 2D response curves superimposed on scatterplots.…”
Section: Referencementioning
confidence: 99%
“…The best growth of INT colonies in this study was found on sites with loose, coarse sand and gravel outwash sediments as opposed to the shale rock overburden that dominates this mine site. Others, working with either INT or the closely related S. exigua [38,46], have also found that INT was generally restricted to coarser-textured sandy soils rather than on heavier-textured clay soils, although in arid areas, a component of finertextured materials can improve the moisture-holding capacity of coarse-textured substrates [45]. By the end of the year of establishment, some plants had already reached heights of 1 m on these gravel outwash deposits and had started to produce RS.…”
Section: Discussionmentioning
confidence: 98%